Difference in Dancing: Two Dance Educators Reflect on Difference in the Dance Studio. Issue 1 (3rd April 2018) - Ssebuuma, Antonio Bukhar; Martin, Rose
ABSTRACT: This article critically explores two dance educators' reflections of difference in dance learning and teaching. We pose the question, How as educators might we facilitate and view difference? What have we learned in our teaching practices that aims to celebrate difference? Through the sharing of narratives and reflections about our experiences of teaching dance to a diversity of students in learning events, we realize the importance of addressing a class as a community of different individual stories and realities while acknowledging commonalities that lie within the difference.